2015
DOI: 10.1016/j.apsb.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and microscopic characterization of five commonly-used testacean traditional Chinese medicines

Abstract: Testacean traditional Chinese medicine (TTCM), derived from the outer shell of sea or freshwater mollusks, is a special and important category of Chinese medicinal materials. To ensure the effective use of TTCM, a comparative identification study was performed on five commonly-used testacean drugs, including Haliotidis Concha, Arcae Concha, Meretricis Concha, Ostreae Concha and Margaritifera Concha (Shijueming, Walengzi, Geqiao, Muli and Zhenzhumu in Chinese, respectively). Typical morphological photographs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…(ii) authentic versus adulterated materials; (iii) authentic versus sulfur-fumigated materials, and (iv) authentic versus dyed materials. The authors found that the UPE could be utilized as a fast, simple, and inexpensive method for identification of herbal materials in comparison to conventional techniques such as morphological and microscopic methods, chromatography and spectrum photometer analyses, molecular biology assays, and biomimetic technologies (Chen et al, 2012;Xu et al, 2015).…”
Section: Ma Nematollahi Et Almentioning
confidence: 99%
“…(ii) authentic versus adulterated materials; (iii) authentic versus sulfur-fumigated materials, and (iv) authentic versus dyed materials. The authors found that the UPE could be utilized as a fast, simple, and inexpensive method for identification of herbal materials in comparison to conventional techniques such as morphological and microscopic methods, chromatography and spectrum photometer analyses, molecular biology assays, and biomimetic technologies (Chen et al, 2012;Xu et al, 2015).…”
Section: Ma Nematollahi Et Almentioning
confidence: 99%
“…Microscopic observation is a common method for the identi cation of Chinese herbal materials [18]. In this study, the powdered velvet antler samples (300-”m particles) were sealed with dilute glycerin when observed under the video capture electron microscope (Model XSZ-N107CCD, Shanghai Guangmi Instrument Co., Ltd., China).…”
Section: Microscopic Observationmentioning
confidence: 99%
“…Microscopic technology has the advantages of speed, simplicity, reliability, requires small samples amounts, and is low cost. This method is applied in many pharmacopoeias (Zhao et al, 2006) and has been successfully used to identify herbal medicines and authenticate Chinese prescriptions (Liu et al, 2011;Kang et al, 2012;Xu et al, 2015). Moreover, histological techniques based on microscopic examination have been used to reveal the characteristics of tissue structure and arrangement of cells that could be used as markers for identifying original sources of plant-derived drugs, such as Aloe vera var.…”
Section: Introductionmentioning
confidence: 99%